GENDER PERSPECTIVES OF TWIN TRANSITION IN AGRICULTURE AND FOOD SECTOR COMPANIES: EMPIRICAL EVIDENCE FROM SERBIA - Paunović, Mihailo; Štrbac, Dijana; Živković, Lazar (Economics of Agriculture, 2024)
This paper investigates the gender perspectives in the twin transition of companies in Serbia’s agriculture and food sector, focusing on their adoption of information and communication technologies (ICT) and green/ environmental activities. Using primary data from computer-assisted telephone interviews, a comprehensive survey was conducted among sector companies. Statistical analysis included descriptive statistics and non-parametric tests to compare differences between groups. The results highlight the significant impact of gender diversity on digitalisation adoption. However, disparities emerge in the green transition, particularly in waste reduction through recycling, raw material reuse, and supplier selection based on environmental criteria. No gender-specific differences were found in reducing harmful emissions or using ecofriendly packaging. This study enhances understanding of gender dynamics in the agri-food sector’s twin transformation and highlights how gender perspectives influence digital and environmental practices. The findings inform policymakers and businesses on promoting gendersensitive strategies for sustainable development and economic growth in Serbia and beyond.